Prediction of Air Flow, Temperature and Humidity Patterns in a Pilot Plant Spray Dryer - Saleh, Saad Nahi (Nahrain University College of Engineering Journal, 2010)
This paper presents the prediction of air flow, humidity and temperature patterns in a cocurrent pilot plant spray dryer fitted with a pressure nozzle using a three dimensional model. The modeling was done with a Computational Fluid Dynamic package (Fluent 6.3), in which the gas phase is modeled as continuum using the Euler approach and the droplet/ particle phase is modeled by the Discrete Phase model (Lagrange approach).Good agreement was obtained with published experimental data where the CFD simulation correctly predicts a fast downward central flowing core and slow recirculation zones near the walls. In this work, the effects of the air flow pattern on droplets trajectories, residence time distribution of droplets and deposition of the droplets on the wall also were investigated where atomizing of pure water was used